Edukasi Bahaya dan Pencegahan Preeklampsia Pada Kehamilan - Marbun, Uliarta; Irnawati, Irnawati (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Background: Many risk factors influence the occurrence of Preeclampsia, such as primigravida, hyperplacentosis, extreme maternal age (less than 20 years and more than 35 years), a family history of Preeclampsia or eclampsia, kidney disease, diabetes mellitus, chronic hypertension already suffered before pregnancy superimposed Preeclampsia and obesity. This devotion aims to overcome the problem of possible low knowledge about the dangers and ways of preventing Preeclampsia. The implementation method of conducting education and evaluating pregnant women the extent of knowledge and awareness of the dangers of Preeclampsia and prevention that can be done during pregnancy, preparation for childbirth to the puerperium. Results: From the results of the pretest analysis, more mothers do not know about Preeclampsia during pregnancy, its dangers and how to prevent it, but after being given education on the dangers and how to prevent Preeclampsia, the post-test results show that almost all mothers understand about Preeclampsia during pregnancy, dangers and how to prevent it. Conclusion: Counseling participants, namely pregnant women who attend the activity, can understand the importance of knowing the dangers of Preeclampsia and how to prevent it and are willing to control blood pressure and urine protein regularly and regularly